Posttransplant sCD30 as a biomarker to predict kidney graft outcome - Süsal, Caner; Opelz, Gerhard (Clinica chimica acta, 2012)
In current clinical praxis, monitoring of immunosuppressive agents in organ transplantation is restricted to measurement of drug blood levels and does not consider the drug's variable effect on the individual patient's immune system. Establishment of biological markers that measure the biological effect of immunosuppressive drugs is desirable and would enable the identification of patients who are at risk of developing rejection, or patients who are suitable for minimization or weaning of immunosuppressive therapy. Several studies demonstrated that the technically simple posttransplant measurement in serum of the T cell activation marker soluble CD30 (sCD30) allows prediction of subsequent graft loss in kidney transplant recipients. sCD30 is a relatively large molecule and therefore an attractive biological marker which is resistant to repeated thawing cycles and temperature differences and easily determined using commercial ELISA. Whether sCD30-based prospective adjustment of immunosuppressive therapy can prevent irreversible graft damage and improve long-term graft outcome awaits evaluation in randomized controlled trials.
Available online 20 October 2011
Gesehen am 13.06.2018